A review on the application of the solid waste for building material - Mohd Fodzi, Muhammad Haikal; Marsi, Noraini; Muhd Rus, Anika Zafiah; Awang, Mariah; Huzaisham, Athirah; Thanasingam, Rupashinii (American Scientific Publishers, 2020)
The present study is an attempt to take an overview on the application of the solid waste for building material such as concrete, cement, tiles, roof, brick and geopolymer. According to the Global Environment Centre (GEC), 23,000 tons of wastes were produce every day, expected rise to 30,000 tons by 2020 and only 5% have been recycled in Malaysia. Increasing of population, rapid urbanization and industrialization affected the increasing of the number of solid waste produced. Based on Department of Statistic Malaysia (DOSM), the population growth rate of 1.1% at 2018 with estimated 32.4 million populations compared to 2017 with 32.0 million populations and estimation of the waste increase by 2020 will occur. This review discusses the incorporation of the solid waste such as fly ash, polystyrene, plastic, sludge, glass and timber dust affect the physical and mechanical properties of the building materials. In addition, this paper reviews the recycling and reusing method of the different solid waste that can be applied to building materials. Most of the building materials such as concrete and bricks mix with the different solid waste show the positive effect by producing the lightweight materials, increased in water absorption, compressive strength, the plasticity of the materials and increasing of energy saving based on various research reviews. The findings and the potential application of the different solid waste in building material may help increasing the sustainable development.